Temsirolimus Partially Rescues the Hutchinson-Gilford Progeria Cellular Phenotype - Gabriel, Diana (PLoS One, 2016)
Hutchinson-Gilford syndrome (HGPS, OMIM 176670, a rare premature aging disorder that leads to death at an average age of 14.7 years due to myocardial infarction or stroke, is caused by mutations in the LMNA gene. Lamins help maintain the shape and stability of the nuclear envelope in addition to regulating DNA replication, DNA transcription, proliferation and differentiation. The LMNA mutation results in the deletion of 50 amino acids from the carboxy-terminal region of prelamin A, producing the truncated, farnesylated protein progerin. The accumulation of progerin in HGPS nuclei causes numerous morphological and functional changes that lead to premature cellular senescence. Attempts to reverse this HGPS phenotype have identified rapamycin, an inhibitor of mammalian target of rapamycin (mTOR), as a drug that is able to rescue the HGPS cellular phenotype by promoting autophagy and reducing progerin accumulation. Rapamycin is an obvious candidate for the treatment of HGPS disease but is difficult to utilize clinically. To further assess rapamycin’s efficacy with regard to proteostasis, mitochondrial function and the degree of DNA damage, we tested temsirolimus, a rapamycin analog with a more favorable pharmacokinetic profile than rapamycin. We report that temsirolimus decreases progerin levels, increases proliferation, reduces misshapen nuclei, and partially ameliorates DNA damage, but does not improve proteasome activity or mitochondrial dysfunction. Our findings suggest that future therapeutic strategies should identify new drug combinations and treatment regimens that target all the dysfunctional hallmarks that characterize HGPS cells.